2016
DOI: 10.1117/1.jbo.21.8.085007
|View full text |Cite
|
Sign up to set email alerts
|

Dual interferometer for dynamic measurement of corneal topography

Abstract: Abstract. The cornea is the anterior most surface of the eye and plays a critical role in vision. A thin fluid layer, the tear film, coats the outer surface of the cornea and serves to protect, nourish, and lubricate the cornea. At the same time, the tear film is responsible for creating a smooth continuous surface, where the majority of refraction takes place in the eye. A significant component of vision quality is determined by the shape of the cornea and stability of the tear film. A dual interferometer sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
(84 reference statements)
0
6
0
1
Order By: Relevance
“…In 2005, Licznerski et al [ 75 ] developed a double path shearing interferometer for corneal topography measurement. In 2016, Micali and Greivenkamp [ 76 ] designed a dual interferometer system for measuring the dynamic corneal topography using two aligned simultaneous phase-shifting polarization-splitting TGIs.…”
Section: Approaches In Measuring the Anterior Segmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2005, Licznerski et al [ 75 ] developed a double path shearing interferometer for corneal topography measurement. In 2016, Micali and Greivenkamp [ 76 ] designed a dual interferometer system for measuring the dynamic corneal topography using two aligned simultaneous phase-shifting polarization-splitting TGIs.…”
Section: Approaches In Measuring the Anterior Segmentmentioning
confidence: 99%
“…These technologies can be employed to achieve the accuracy of several micrometers but only cover the corneal region [ 43 ]. Moreover, it is imperative to instill fluorescein to the tear film as a diffusing agent for distinctly imaging the anterior corneal shape [ 67 , 76 , 80 ]. Additionally, the major drawback is that the low-pass filter should be inevitably applied during the interference fringe processing.…”
Section: Approaches In Measuring the Anterior Segmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Metode yang digunakan pada topografi korena dapat dibagi menjadi dua kategori: metode berbasis refleksi dan metode berbasis proyeksi. Metode berbasis refleksi diantaranya adalah penggunaan pola lingkaran Placido, keratometer, dan videokeratoskopi, sedangkan contoh topografi kornea berbasis proyeksi adalah Scheimpflug pattern, slit photography, rasterstereofotografi, dan beragam metode interferometry [4], [11], [12] .…”
Section: Pendahuluanunclassified
“…Recently D. Micali et al [55] reported the reconstruction of the corneal topography using a pair of polarization-splitting Twyman-Green interferometers by polarization division. This interferometer had a dynamic range of surface of 256…”
Section: R Iyer Et Almentioning
confidence: 99%